blaKPC-24-Harboring Aeromonas veronii from the Hospital Sewage Samples in China - Chengcheng Yang; Min Guo; Haizhen Yang; Yicheng Wen; Zhichen Zhu; Tao Wang; Jie Zhu; Liang Chen; Hong Du (Microbiology Spectrum, 2022)
ABSTRACT KPC-24, different from KPC-2 by a single amino acid alteration at codon 6 (R6P), was initially discovered in Klebsiella pneumoniae in Chile. Here, we reported KPC-24-producing Aeromonas veronii isolates from hospital sewage in China. The blaKPC-24 was cloned and the MICs were tested against β-lactams antimicrobial agents. KPC-24 exhibited a β-lactam susceptibility profile similar to that of KPC-2. Whole-genome sequencing and analysis revealed that blaKPC-24 was located within a Tn6296-related region on an IncP-6 plasmid. IMPORTANCE Our study described a variant of K. pneumoniae carbapenemase (KPC), KPC-24, from two A. veronii strains isolated from hospital sewage, in which antibiotics, biocides, pharmaceuticals, and heavy metals may supply an appropriate condition for the evolution of carbapenemases. Some variants exhibited stronger hydrolysis activity to antibiotics and gave rise to a major public health concern. More seriously, Aeromonas species are prevalent in aquatic environments and, thus, may act as a suitable vector for antibiotics-resistance genes and foster the transmission of resistance. We should attach importance to surveying the evolution and transmission of antibiotics-resistance genes.